2021
DOI: 10.1016/j.bja.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, mortality, and systems safety in non-operating room anaesthesia: a narrative review

Abstract: Non-operating room anaesthesia (NORA) describes anaesthesia delivered outside a traditional operating room (OR) setting. Non-operating room anaesthesia cases have increased significantly in the last 20 yr and are projected to account for half of all anaesthetics delivered in the next decade. In contrast to most other medication administration contexts, NORA is performed in high-volume fast-paced environments not optimised for anaesthesia care. These predisposing factors combined with increasing case volume, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“… 14 A narrative review found higher rates of morbidity and mortality in non-operating room anaesthesia, and one of the main reasons was limited preoperative evaluation. 6 In this systematic review, the assessment of PAC was significantly associated with reduced mortality following complex orthopaedic surgery in only one study. 34 Retrospective studies have reported similar results, but with different surgeries.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… 14 A narrative review found higher rates of morbidity and mortality in non-operating room anaesthesia, and one of the main reasons was limited preoperative evaluation. 6 In this systematic review, the assessment of PAC was significantly associated with reduced mortality following complex orthopaedic surgery in only one study. 34 Retrospective studies have reported similar results, but with different surgeries.…”
Section: Discussionmentioning
confidence: 86%
“… 4 However, a previous review found higher rates of morbidity and mortality in non-operating room anaesthesia, which was attributed to limited preoperative evaluation. 6 A retrospective study found significant associations between perioperative mortality and age <1 year or >65 years, American Society of Anesthesiologists (ASA) Physical Status Classification System, emergency case status and operative start time after 18:00. 7 This might indicate that risk factors are both patient and surgery related and may be linked to organisational structures.…”
Section: Introductionmentioning
confidence: 99%
“…Working in unfamiliar perioperative environments has also been associated with increased morbidity. In a narrative review of factors contributing to morbidity, mortality, and safety concerns in non-OT anaesthesia locations, Herman et al (2021) reported a lack of familiarity regarding the team, location, and equipment as contributing concerns. Furthermore, as shown by Frasier et al (2019), a decreased familiarity between perioperative team members is also associated with reduced cross-disciplinary communication; Wacker and Kolbe (2014) report that these scenarios can negatively impact patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘systems approach’ to safety suggests that accidental harm may be perpetuated by inadequacies in work system design [8 ▪ ]. Numerous safety systems have been proposed to provide hospitals and care providers a framework by which meaningful advances in the safety of patient care may be achieved.…”
Section: Introductionmentioning
confidence: 99%